Nb 첨가 오스테나이트계 내열 스테인리스강의 열기계적 피로 수명 및 변형 거동 - 오용준; Yong Jun Oh; 박중철; Joong Cheul Park; 양원존; Won Jon Yang (대한금속·재료학회지, 49(7), 2011)
Thermomechanical fatigue (TMF) behavior of heat resistant austenitic stainless steel was evaluated in the temperature range from 100℃ to peak temperatures of 600 to 800℃; The fatigue lives under TMF conditions were plotted against the plastic strain range and the dissipated energy per cycle. In the expression of the inelastic strain range versus fatigue life, the TMF data obtained at different temperature ranges were located close to a single line with a small deviation; however, when the dissipated energy per cycle, calculated from the area of the stress-strain hysteresis loops at the half of the fatigue life, was plotted against the fatigue life, the data showed greater scattering than the TMF life against the inelastic strain range. A noticeable stress relaxation in the stress-strain hysteresis curve took place at the peak temperatures higher than 700℃, but all specimens in this study exhibited cyclic hardening behavior with TMF cycles. Re-crystallization occurred during the TMF cycle concurrent with the formation of fine subgrains in the re-crystallized region, which is considered to cause the cyclic hardening of the steel.